2011
DOI: 10.1074/jbc.m110.165951
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nuclear Localization, DNA Binding, and Transactivating Mechanisms of Krüppel-like Zinc Finger Protein Gli-Similar 2 (Glis2)

Abstract: Gli-similar 1-3 (Glis1-3) constitute a subfamily of Krüppel-like zinc finger (ZF) transcription factors that are closely related to the Gli protein family. Mutations in GLIS2 are linked to nephronophthisis, a chronic kidney disease characterized by renal fibrosis and atrophy in children and young adults. Currently, very little information exists about the mechanism of action of Glis2, its target genes, or the signaling pathways that regulate its activity. In this study, we show that a region within ZF3 is requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 29 publications
2
37
0
Order By: Relevance
“…We speculated that the TRIM32-mediated shift in Glis2 K48/ K63 polyubiquitylation may also alter the interaction partners of Glis2, affecting its subcellular localization. Immunofluorescence experiments in HEK 293T cells using YFP-tagged Glis2 (YFP.Glis2) revealed a diffuse nuclear localization of Glis2 consistent with previous observations (18) (Fig. 8A).…”
Section: Trim32 Promotes the Accumulation Of K63-linkedsupporting
confidence: 74%
See 2 more Smart Citations
“…We speculated that the TRIM32-mediated shift in Glis2 K48/ K63 polyubiquitylation may also alter the interaction partners of Glis2, affecting its subcellular localization. Immunofluorescence experiments in HEK 293T cells using YFP-tagged Glis2 (YFP.Glis2) revealed a diffuse nuclear localization of Glis2 consistent with previous observations (18) (Fig. 8A).…”
Section: Trim32 Promotes the Accumulation Of K63-linkedsupporting
confidence: 74%
“…10A). Although Glis2 interacts with CtBP1 to function as a transcriptional repressor in most instances (12), Glis2 activates the mIns2 (mouse insulin-2) promoter by binding to the Glis binding sites of the mIns2 promoter (18). Here, TRIM32 had a modest repressor function, inhibiting the Glis2-mediated mIns2 activation by ϳ50% (Fig.…”
Section: Trim32 Promotes the Accumulation Of K63-linkedmentioning
confidence: 99%
See 1 more Smart Citation
“…7B). Previously, we reported that Glis2 was able to activate the mIP(Ϫ696)-Luc reporter in HEK293 cells (21). We therefore examined whether SUFU had any effect on the transactivation of the Ins2 promoter by Glis2.…”
Section: The Region Of Glis3 Between Amino Acids 296 and 354 Is Highlmentioning
confidence: 99%
“…Generation of Reporter and Expression Constructs-The generation of p3xFlag-CMV-Glis1, p3xFlag-CMV-Glis2, p3xFlag-CMV-Glis3, p3xFlagCMV-Glis3⌬N302, p3xFlag-CMVGlis2⌬N58, p3xFlag-CMV-Glis2⌬N160, and p3xFlag-CMVGlis2⌬C169 was described previously (6,9,20,21). The plasmids p3xFlag-CMV-Glis3⌬N34, -65, -155, -288, -295, -319, -333, -355, and -388 and p3xFlag-CMV-Glis3⌬C389 were generated by PCR amplification of the respective fragments and inserting them into the EcoRI and BamHI restriction sites of the p3xFlag-CMV10 expression vector (Sigma).…”
Section: Cells and Growth Conditions-rat Insulinoma Ins-1832/13mentioning
confidence: 99%